Table of Content - - (Journal of Educational and Psychological Sciences, 2023)
Table of Content: 1. The impact of digital transformation in general education schools in facing challenges and continuous developments in the world from the point of view of teachers in Makkah Al-Mukarramah region Mr. Maher Abdulrahman Alnemari 2. Attitudes of Science Teachers towards Development of Physical Concepts using Virtual laboratories and their Obstacles Mr. Abdullah Sahal Al-Otibi 3. Attitudes of Primary Stage Teachers Towards the Use of Active Learning Methods in Teaching in Sahab Brigade Schools in Amman Governorate Mrs. Weam Waleed Abbas 4. Application Requirements for E-management in Yemeni Ministry of Youth and Sports Prof. Hussein Salah Juaim, Mr. Kamal Ali Ahmed 5. Wisdom-based Thinking and Hexagonal Achievement Goal Approaches of Outstanding and Superior Students in the Secondary Stage in Makkah City Mrs. Shurog Ahmed Alshehri, Co-Prof. Yasser Abdullah Hefny 6. The Psychometric Characteristics of a scale for parental emotional blackmail Mrs. Lamia Ibrahim Alshamsan, Prof. Sufyan Ibrahim Alrebdi 7. The level of school bullying with middle school stage pupils - A field study at middle schools in Algiers- Dr. Abib Ghania, Dr. Lallouche Saliha